158k views
3 votes
Derivative of these questions


Derivative of these questions ​-example-1
User Prranay
by
5.9k points

1 Answer

6 votes

Answer:
\bold{y'=(1)/(2(a-b)^2)\bigg((1)/(√(x+a))+(1)/(√(x+b))\bigg)}

Explanation:


y=(1)/(√(x+a)-√(x+b))\\\\\\\text{Rationalize the denominator:}\\y=(1)/(√(x+a)-√(x+b))\bigg((√(x+a)+√(x+b))/(√(x+a)+√(x+b))\bigg)\\\\\\y=(√(x+a)+√(x+b))/(x+a-x-b)\\\\\\y=(√(x+a)+√(x+b))/(a-b)\\\\\\\text{Apply the derivative (derivative of the numerator (top) divided by the}\\\text{denominator (bottom) squared).}


\text{Derivative of }√(x+a)\quad \rightarrow \quad (x+a)^{(1)/(2)}\quad = \quad (1)/(2)(x + a)^{-(1)/(2)}\\\\\text{Derivative of }√(x+b)\quad \rightarrow \quad (x+b)^{(1)/(2)}\quad = \quad (1)/(2)(x + b)^{-(1)/(2)}\\\\\\\text{Derivative of}\ (√(x+a)+√(x+b))/(a-b):\\\\= \frac{(1)/(2)(x + a)^{-(1)/(2)}+(1)/(2)(x + b)^{-(1)/(2)}}{(a-b)^2}


\text{Factor out }(1)/(2)\ \text{from the numerator:}\\\\\frac{(x+a)^{-(1)/(2)}+(x+b)^{-(1)/(2)}}{2(a-b)^2}\\\\\\\text{Move the terms with negative exponents to the denominator:}\\\\=(1)/(2(a-b)^2)\bigg((1)/(√(x+a))+(1)/(√(x+b))\bigg)

User KickinMhl
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.